2016
DOI: 10.1108/bepam-02-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Building management system for sustainable built environment in Sri Lanka

Abstract: Purpose – The purpose of this paper is to investigate the contribution of building management system (BMS) towards a sustainable built environment. Design/methodology/approach – The paper is based on the findings of a comprehensive literature survey, preliminary survey and a structured questionnaire survey. Quantitative data were analysed using a relative importance index. Content analysis was used for the qualitative data analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In the building sector, achieving sustainability is a key challenge due to its unlimited resource consumption (Kumara et al, 2016). Having sustainable construction goals is important to achieve economic, social and environmental parameters of the sustainable development (Adetunji et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the building sector, achieving sustainability is a key challenge due to its unlimited resource consumption (Kumara et al, 2016). Having sustainable construction goals is important to achieve economic, social and environmental parameters of the sustainable development (Adetunji et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Kumara et al [18] investigated whether and how BMS can contribute to a sustainable built environment. They conducted a comprehensive literature review and identified some core attributes of BMS.…”
Section: Smart Building Management System (Sbms) Attributesmentioning
confidence: 99%
“…These attributes include starting/stopping building systems optimally, enabling the monitoring and control of building facilities, supporting optimal equipment time scheduling, enabling alarm settings and automatic notification, and en-suring building safety. Kumara et al [18] invited a small group of building professionals (25 of them) to take part in a questionnaire survey. They reported that participants ranked real time monitoring as the most important attribute of BMS, followed by trend analysis, and alarm reporting.…”
Section: Smart Building Management System (Sbms) Attributesmentioning
confidence: 99%
“…Also, it has been applied in order to study the energy performance of buildings [134,135], optimization of multidimensional modeling for decision support [136], and with smart buildings [112,134]. However, there is a number of techniques implemented to analyze and measure comfort of occupants in terms of indoor quality and operational management based to reduce the energy-use [137].…”
Section: D) Analysis-oriented Ems-in-bsmentioning
confidence: 99%